Retiree health benefit coverage and retirement - James Marton; Stephen A. Woodbury (Levy Economics Institute of Bard College, 2006)
Employer-provided health benefits for workers who retire before age 65 has fallen over the last decade. We examine a cohort of male workers from the Health and Retirement Survey to explore the dynamics of retiree health benefits and the relationship between retiree health benefits and retirement behavior. A better understanding of this relationship is important to the policy debate over the best way to increase health coverage for older Americans without reducing work incentives. Concerning the dynamics at work, we find that, between 1992 and 1996, 24 percent of full-time workers who had retiree health benefits lost their coverage, while 15 percent of full-time workers who lacked coverage gained it. Also, of the full-time employed men who were covered by retiree health benefits in 1992 and had retired by 1996, 3 percent were uninsured, and 15 percent were covered by health insurance other than employer-provided insurance. On the relationship between retiree health benefits and retirement, we find that workers with retiree benefits were 29 to 55 percent more likely to retire than those without. We also find that workers who are eligible for retiree health benefits tend to take advantage of them when they are relatively young.
Keywords: J26; J32; J33; I18; M52; 330; Health insurance; employee benefits; retirement; elderly; employment; retiree; health benefits